2017
DOI: 10.1167/17.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of content in recently-viewed scenes whitens perception

Abstract: Anisotropies in visual perception have often been presumed to reflect an evolutionary adaptation to an environment with a particular anisotropy. Here, we adapt observers to globally-atypical environments presented in virtual reality to assess the malleability of this well-known perceptual anisotropy. Results showed that the typical bias in orientation perception was in fact altered as a result of recent experience. Application of Bayesian modeling indicates that these global changes of the recently-viewed envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 43 publications
3
32
1
Order By: Relevance
“…These results accord well with the recent work of Schweinhart et al. (2017), who exposed participants to anisotropic training content within a virtual reality system to induce a perceptual change similarly reflecting the properties of their training stimuli.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results accord well with the recent work of Schweinhart et al. (2017), who exposed participants to anisotropic training content within a virtual reality system to induce a perceptual change similarly reflecting the properties of their training stimuli.…”
Section: Discussionsupporting
confidence: 91%
“…Eyetracking contour detection data from these participants were compared with data from control subjects who were instructed to limit exposure to screens for the same period of time. Schweinhart et al. (2017) demonstrated that the visual system is capable of adapting to anisotropic scene statistics but used unrealistic stimuli with respect to what exists in the real world.…”
Section: Experiments 2: Mindcraft: Increasing the Oblique Effect With mentioning
confidence: 99%
See 1 more Smart Citation
“…Dong and Atick, 1995;Field, 1987;Geisler, 2008;Hansen and Essock, 2005;427 Simoncelli and Olshausen, 2001). Our findings here imply that as well as having a preference 428 for external stimuli with naturalistic properties, the internal structure of the visual system 429 might itself have evolved to emulate these temporal constraints (Field, 1987;Haun and Peli, 430 2013; Schwartz and Simoncelli, 2001;Schweinhart et al, 2017). 431 432…”
mentioning
confidence: 79%
“…More subtle manipulations of the environment have also been explored recently (Schweinhart et al, 2017). Natural images contain the most content around horizontal orientations, the second most around vertical orientations, and the least near oblique orientations (±45°).…”
Section: Using Altered Reality To Study Long-term Contrast Adaptationmentioning
confidence: 99%